2021 IEEE International Symposium on Circuits and Systems (ISCAS) 2021
DOI: 10.1109/iscas51556.2021.9401300
|View full text |Cite
|
Sign up to set email alerts
|

A 1D-CNN Based Deep Learning Technique for Sleep Apnea Detection in IoT Sensors

Abstract: Internet of Things (IoT) enabled wearable sensors for health monitoring are widely used to reduce the cost of personal healthcare and improve quality of life. The sleep apneahypopnea syndrome, characterized by the abnormal reduction or pause in breathing, greatly affects the quality of sleep of an individual. This paper introduces a novel method for apnea detection (pause in breathing) from electrocardiogram (ECG) signals obtained from wearable devices. The novelty stems from the high resolution of apnea detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 19 publications
(17 reference statements)
0
5
0
Order By: Relevance
“…Kim et al [35] explored various machine learning models such as Logistic Regression, Random Forest, XGBoost as well as SVM and concluded that SVM showed the best result in their study. Many others imported assorted deep learning techniques such as various adaptations of CNN [7], [15], [16], [19], [38] or other deep learning models [11], [37] in an attempt to classify patients with OSA. Others used different biosignals such as SpO2 [39] or respiration signals such as Oronasal thermal airflow (FlowTh), Nasal pressure (NPRE), and abdominal respiratory inductance plethysmography (ABD) [40].…”
Section: Related Workmentioning
confidence: 99%
“…Kim et al [35] explored various machine learning models such as Logistic Regression, Random Forest, XGBoost as well as SVM and concluded that SVM showed the best result in their study. Many others imported assorted deep learning techniques such as various adaptations of CNN [7], [15], [16], [19], [38] or other deep learning models [11], [37] in an attempt to classify patients with OSA. Others used different biosignals such as SpO2 [39] or respiration signals such as Oronasal thermal airflow (FlowTh), Nasal pressure (NPRE), and abdominal respiratory inductance plethysmography (ABD) [40].…”
Section: Related Workmentioning
confidence: 99%
“…TinyML opens up a broad spectrum of real-time and lowfootprint eHealth applications, some of which are summarized in Table XVI. These include monitoring eating episodes and coughs using microphones [221], [223], sleep monitoring and arrhythmia detection through ECG measurements [171], [222], epileptic seizure recognition from EEG sensors [171], and fall detection using earable inertial sensors [2]. Most TinyML mHealth applications are variants of anomaly detection, indicating the presence or the absence of a health condition, thereby allowing the use of ultralightweight models in the order of 10 0 -10 1 kB.…”
Section: F Mhealthmentioning
confidence: 99%
“…Most TinyML mHealth applications are variants of anomaly detection, indicating the presence or the absence of a health condition, thereby allowing the use of ultralightweight models in the order of 10 0 -10 1 kB. Example models for mHealth include Bonsai [2], embedded GRU [221], 1-D CNN [222], FC-AE [171], and two-layer CNN/LSTM [223].…”
Section: F Mhealthmentioning
confidence: 99%
“…Following previous studies (Mostafa et al, 2017(Mostafa et al, , 2020, we labeled a 1 min segment as SA if the segment contains more than 5 s of SA events. Considering the class imbalance problem of UCDDB, the data of patients without SA events (ucddb008, ucddb011, ucddb013, and ucddb018) are not used (John et al, 2021).…”
Section: University College Dublin Sleep Apnea Database (Ucddb)mentioning
confidence: 99%